G276 Faster Clean Catch Urine Collection from Infants: The Quick-Wee Randomised Controlled Trial. (24th May 2017) - Kaufman, J; Fitzpatrick, P; Tosif, S; Hopper, S; Donath, S; Bryant, P; Babl, F
Abstract : Aims: Urinary tract infection is common and important to diagnose or exclude in febrile young children. Limitations exist with current urine collection methods and clinician collection preferences vary. UK NICE Guidelines recommend clean catch urine (CCU) which is convenient but can be unreliable and time-consuming. An ideal urine collection method would be simple, fast and require minimal resources. We evaluate if a novel voiding stimulation method can increase the rate of infant voiding for CCU within 5 min. Method: Randomised controlled trial of infants aged 1–12 months requiring urine collection in a tertiary paediatric hospital emergency department. Following standard perigenital cleaning, patients were randomised to either the novel 'Quick-Wee' method (gentle cutaneous suprapubic stimulation with cold saline-soaked gauze), or standard CCU (no stimulation). Primary outcome: Void within 5 min. Secondary outcomes: Successful catch of sample, parental/ clinician satisfaction with technique, contamination rate. Results: 344 patients included in the analysis, 50% male, mean age 5.5 months. 31% (54/174) voided within 5 min with Quick-Wee, 11.8% (20/170) with standard CCU, difference in proportions 19.2% (95%CI for difference 10.9%–27.7%). The risk ratio for voiding with Quick-Wee compared with standard CCU was 2.6. compared with standard CCU, Quick-Wee had higher rates of successfully catching urine, higher parental and clinician satisfaction, and lower contamination. Conclusion: Cold fluid suprapubic stimulation can trigger voiding in infants, and improves the success of CCU within 5 min in the emergency department.